Decoupling the Core: A Technical Roadmap for Modernizing Mainframe into Cloud-Native Microservices on Azure Kubernetes Service - Tathagata Roy (Eastasouth Institute, 2024)
Modernizing tightly coupled mainframe ecosystems built on COBOL business logic, CICS transaction flows, CA7 batch schedules, and DB2/VSAM data structures remains a technically complex undertaking for enterprises seeking cloud‑native agility. This paper presents a structured roadmap for decomposing monolithic mainframe workloads into Spring Boot microservices deployed on Azure Kubernetes Service, supported by Kafka for asynchronous, event‑driven communication. The work examines the translation of COBOL Copybooks into JSON or Avro schemas for API‑driven interoperability, the extraction of COBOL and stored‑procedure logic into Spring Data and service layers, and the re‑engineering of JCL utilities into containerized batch pipelines orchestrated through Kubernetes‑native schedulers. It also evaluates approaches for transforming 3270 CICS interfaces into modern React or Spring Thymeleaf frontends, migrating IBM MQ patterns into Kafka‑aligned messaging, and integrating RACF‑based security models with cloud identity providers. Automated code‑analysis and refactoring tools available at the time of writing are assessed for their ability to accelerate large‑scale modernization while preserving transactional integrity and regulatory compliance. The resulting roadmap provides a technically grounded strategy for decoupling mainframe cores and transitioning toward resilient, modular, and cloud‑aligned architectures.